THE DEVELOPMENT INDICATOR OF SUCCESS STUDENT’S PARTICIPATION IN CLASSROOM MANAGEMENT FOR SECONDARY SCHOOL IN NORTHEAST - Srepila, Aduldej; Budeesuwan, Sujin; Lumana, Preeda (Journal of Buddhist Anthropology, 2020)
The objective of this research was: to study the current situation of classroom management of secondary school in northeast, and develop the indicators of success Student’s Participation in Classroom Management for Secondary School in Northeast. This Mix-method research. The research study was divided into 2 phases as follows: Phase 1 were study the current situation of classroom management of secondary school in northeast quantitative research methods. The sample consisted 274 schools. Students sample group of room 1 per school, 10 persons per room, a total 2,740 people 5 teachers in each school, totaling 1,370 persons. Sample by Cluster Random Sampling and Sample Random Sampling. The instrument used as a questionnaire for estimating 5 levels with discrimination between 0.244 to 8.675 and reliability of 0.977. The data analysis included the Mean and Standard Deviation. Phase 2 was developing the indicators of success classroom management of secondary school in northeast quantitative research methods. Use Purposively selected by 18 participants, tools as item records, and the data analysis included the content analysis. The research findings were as follows: According to the study and investigation of current situation of classroom management from secondary school in northeast the overall at a medium level ( = 3.00, S.D. = 2.24). And the findings of analysis indicator of success in the student’s participation in classroom management by organizing the Workshop Participatory Creative, the implementation of conference for teamwork’s collaboration in brainstorming, 3 aspects of indicator for success in activity organization, were determined including: 22 indicators of learning management participation, 30 indicators of classroom disciplines, and 20 indicators of classroom atmosphere